New species of Blaesodactylus (Squamata: Gekkonidae) from Ankarafantsika National Park in north-western Madagascar - Bauer, Aaron M.; Glaw, Frank; Gehring, Philip-Sebastian; Vences, Miguel (Zootaxa, 2011)
We describe a new gecko of the genus Blaesodactylus from dry forest in Ankarafantsika National Park, western Madagascar. Blaesodactylus ambonihazo sp. nov. is distinguished by its medium size, small and homogeneous gular granules, unspotted ventral side, and lack of tubercles on distal part of original tail. The new species, for which we propose an IUCN Red List status of "Data Deficient", is also characterized by a strong differentiation in the mitochondrial DNA and a unique haplotype in the nuclear Rag-1 gene. The molecular data presented herein also confirm new locality records of Blaesodactylus antongilensis along the Malagasy east coast (Ambodiriana, Andaparaty, Befanjana and Sahafina). Within its known distribution area this species is genetically homogeneous in the markers studied. In contrast, the population of B. sakalava from the Tsingy de Bemaraha in central western Madagascar is genetically divergent compared to south-western specimens and needs further morphological and genetic studies to clarify its taxonomic status.